A computer–controlled active suspension for a wheeled terrain robot. (4th August 2014) - Tani, Kazuo; Usui, Seiichi; Horiuchi, Eiichi; Shirai, Nobumasa; Hirobe, Shinji
The aim of our study is to propose a mechanism and control methods for an active suspension and to experimentally demonstrate its applicability to wheeled terrain robots. We built a one–wheel experimental hardware model which includes a mechanism of the suspension, a direct–drive DC servo motor as the actuator, passive elements such as springs and dampers, sensors, and a computer configuration. We implemented PID control and optimal control. We restricted ourselves to the use of only internal sensors for the control: a potentiometer for the body–axle distance and an accelerometer for the body displacement. Simulations showed that an active suspension enables a vehicle to pass over higher steps than a passive or no suspension.